Circulating MicroRNA-30d Is Associated With Response to Cardiac Resynchronization Therapy in Heart Failure and Regulates Cardiomyocyte Apoptosis: A Translational Pilot Study. Issue 25 (23rd June 2015) - Melman, Yonathan F.; Shah, Ravi; Danielson, Kirsty; Xiao, Junjie; Simonson, Bridget; Barth, Andreas; Chakir, Khalid; Lewis, Gregory D.; Lavender, Zachary; Truong, Quynh A.; Kleber, Andre; Das, Ranendra; et al.
Abstract : Background—: Biomarkers that predict response to cardiac resynchronization therapy (CRT) in heart failure patients with dyssynchrony (HFDYS ) would be clinically important. Circulating extracellular microRNAs (miRNAs) have emerged as novel biomarkers that may also play important functional roles, but their relevance as markers for CRT response has not been examined. Methods and Results—: Comprehensive miRNA polymerase chain reaction arrays were used to assess baseline levels of 766 plasma miRNAs in patients undergoing clinically indicated CRT in an initial discovery set (n=12) with and without subsequent echocardiographic improvement at 6 months after CRT. Validation of candidate miRNAs in 61 additional patients confirmed that baseline plasma miR-30d was associated with CRT response (defined as an increase in left ventricular ejection fraction ≥10%). MiR-30d was enriched in coronary sinus blood and increased in late-contracting myocardium in a canine model of HFDYS, indicating cardiac origin with maximal expression in areas of high mechanical stress. We examined the functional effects of miR-30d in cultured cardiomyocytes and determined that miR-30d is expressed in cardiomyocytes and released in vesicles in response to mechanical stress. Overexpression of miR-30d in cultured cardiomyocytes led to cardiomyocyte growth and protected against apoptosis by targeting the mitogen-associated kinase 4, a downstream effector of tumor necrosis factor. In HFDYS patients, miR-30d plasma levels inversely correlated with high-sensitivity troponin T, a marker of myocardial necrosis. Conclusions—: Baseline plasma miR-30d level is associated with response to CRT in HFDYS in this translational pilot study. MiR-30d increase in cardiomyocytes correlates with areas of increased wall stress in HFDYS and is protective against deleterious tumor necrosis factor signaling. Abstract : Supplemental Digital Content is available in the text.